2007 Annual report. The contribution of IICA to agriculture and the development of rural communities in Belize - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2021)
In 2007, IICA presents the implementation of the Medium-Term Institute 2006-2010 Plan, with the objective of creating a model institution for modern development and implementation of components of the institute's vision for the promotion of rural sustainability in the development of agriculture. food safety and security and rural prosperity. The technical program executed in 2007 is a direct result of the demands and adjustments in the sector to guarantee the safety and security of food, commerce and the general development of the sector. Included technical activities with the public sector along with key interventions in support of the main industries of the sector.